Insights into the Drug Repositioning Applied to the Alzheimer's Disease Treatment and Future Perspectives - de Castro, Alexandre A; da Cunha, Elaine F F; Pereira, Ander F; Soares, Flavia V; Leal, Daniel H S; Kuca, Kamil; Ramalho, Teodorico C (Current Alzheimer research, 2018)
Alzheimer's disease is known to be a chronic disease, with an estimated prevalence of about 10-30%, considering the population over 60 years of age. Most patients with this disorder (> 95%) present the sporadic form, being characterized by a late onset (80-90 years of age), and it is the consequence of the failure to clear the amyloid-β (Aβ) peptide from the interstices of the brain. Significant numbers of genetic risk factors for the sporadic disease have been researched. Some existing drugs for Alzheimer's disease provide symptomatic benefit for up to 12 months, but there are no approved disease- modifying therapies. In this line, a complementary strategy based on repositioning drugs which are approved for the treatment of other disorders could be interesting. It is noteworthy the fact that some clinical trials indicate that several classes of drugs own potent and beneficial effects on the Alzheimer's disease treatment. In this present work, we present the details and evaluation of these alternative treatments. It has highlighted several compounds with relevant evidence for this purpose, which deserves further investigation to clarify optimal treatment conditions in the clinical trials of patients with Alzheimer's disease.
Keywords: neurodegeneration; senioři nad 80 let; Alzheimer’s disease; drug repositioning; mužské pohlaví; Drug Repositioning; Alzheimer Disease; přehodnocení terapeutických indikací léčivého přípravku; Antipsychotic Agents; pharmacophores; Aged, 80 and over; ženské pohlaví; Humans; antipsychotika; amyloid-β peptide; Alzheimerova nemoc; Female; tau protein.; lidé; Male